Fascinating Digital Marketing, Excellent Service, Brand Awareness, Tactics That Can Help Business Grow During Pandemic on SMSEs Culinary Tourism - Eman Sulaiman; Ellin Herlina; Vina Andita Pertiwi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
This study objectives to decide the impact of Digital Marketing on Sales Volume, to determine Excellent Service on Sales Volume, and to determine the effect of Brand Awareness on Sales Volume in culinary MSME businesses during the pandemic in Cirebon. The data analysis technique used the Statistical Package for the Social Sciences method, the data collection method uses an online form questionnaire to culinary entrepreneurs in Cirebon. The sampling technique used the probability sampling method with a sample size of 74 respondents. Based on the study results, it can be concluded that Digital Marketing, Excellent Service, Brand Awareness has a positive effect on sales volume during the Covid 19 pandemic in culinary MSME businesses in Cirebon.